Knowledge of Mothers with Children Aged 0-24 Months on Child Nutrition - Gülperi Demir; Hülya Yardımcı; Funda Pınar Çakıroğlu; Ayşe Özfer Özçelik (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Adequate and balanced nutrition plays an important role in the healthy growth and development of children. The main problem related to nutrition in children derives from the fact that mothers do not have enough knowledge on nutrition. Determining the nutritional knowledge of the mothers, identifying the deficiencies and mistakes and transferring the correct one instead of them is important for raising healthy generations. The aim of this study is to determine the knowledge of mothers with children between 0-24 months old about child nutrition and to evaluate them according to various variables. The descriptive study was conducted on mothers n:250 with children between 0-24 months old. Data were obtained via questionnaire form. The questionnaire included 20 knowledge statements on child nutrition. The data were analyzed using IBMSPSS 20.0 for statistical program. Ages of mother’s and children’s, mothers’ employment status and educational levels, birth order of children in the family and the mother's knowledge sources were used as variables to evaluate the maternal nutritional knowledge of the mothers. For the analysis, independent sample t-test and One-way Anova were used. The average knowledge scores of the mothers was 15.4±1.5; 75.0.% of the highest possible score of 20. When knowledge scores of the mothers were analyzed by variables, a significant difference was found between their scores according to age. This difference was due to the 26-30 age group 15.7±1.2 score, p